Competing for the Apocalypse: Religious Rivalry and Millennial Transformations in a Japanese New Religion - Baffelli, Erica (International journal for the study of new religions, 2011)
This article examines how one Japanese new religion shifted its orientations and perspectives--notably in millennialist terms--in the late twentieth century, and suggests this may have been influenced by the rivalries and conflicts it had with another millennialist movement in Japan. By examining the rivalry between Aum Shinrikyo and Kofuku no Kagaku, and by examining how the activities of each impacted on those of the other, we can see how religious groups do not formulate policies and teachings, or amend their perspective on the world, in isolation. We argue that while looking at the prevailing religious trends of any era can help us understand the specific teachings of individual groups, we should also pay attention to the interactions between groups. It also suggests that when we discuss categories and types of millennialism, we should be aware that movements can encapsulate more than one form of millennialism at any one time.